Hak Kekayaan Intelektual (HaKI) dalam Perspektif Hukum Islam - Quraisy, Mujahid (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
This research started from the need for appreciation to intellectuality, creativity and ideas of every individual, which is known as the Intellectual Property Rights (IPR). The problem arises when IPR was crashed with the mission of learning and empowerment for the benefit of the people. The result of this study was that intellectual property could become public goods if used as a means or tool to achieve the objectives of production, distribution and consumption in order to improve their quality. However, it is done without losing the identity of the inventor and the responsibility of government to procure. Intellectual property as private property becomes syubhat for others in taking it if it is associated with personal goals. In other words, the Intellectual Property becomes halal if it comes from the source of the original owner if it is given as a gift. It is becomes unlawful if it used in according with the goal for both commercial production and distribution levels